2008
DOI: 10.4322/rbeb.2012.054
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação eletromiográfica quantitativa de músculos faciais em crianças do sexo feminino com mordida cruzada

Abstract: The electromyography has been widely used as a diagnostic method for facial muscle conditions. The aim of this study was to determine the RMS (Root Mean Square) value of the electromyographic signal of facial muscles in children with normal occlusion or cross-bite as well as to verify a possible clinical application of this parameter. "Normal group" was composed of female children with normal occlusion and "cross-bite group" was composed of female children with cross-bite. We performed quantitative electromyog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
2
0
3
Order By: Relevance
“…Two methods are used to assess the differences among EMG signals. First, the root means square (RMS) value of the myoelectric signal is a commonly utilized method that reflects the level of the physiological activities in the motor unit during contraction [ 132 ]. Most of the studies showed that a massage could not alter the electromyographic characteristics of muscles [ 34 , 44 , 95 , 113 , 114 , 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…Two methods are used to assess the differences among EMG signals. First, the root means square (RMS) value of the myoelectric signal is a commonly utilized method that reflects the level of the physiological activities in the motor unit during contraction [ 132 ]. Most of the studies showed that a massage could not alter the electromyographic characteristics of muscles [ 34 , 44 , 95 , 113 , 114 , 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Neuro-EMG-Micro EMG device was used to record the EMG signals and the root mean square (RMS) was calculated and used for analysis. The RMS was chosen as it reflects the level of physiological activity in the motor unit during contraction [35]. The outcome measures were the RMS values of the myoelectric activity of the VMo and VL muscles as well as the VMo/VL muscle ratio during stair climbing and single leg mini-squat.…”
Section: Emg Data Analysismentioning
confidence: 99%
“…Seguindo determinação de De Luca [22] posicionamos o eletrodo na linha média do ventre muscular no sentido perpendicular ao comprimento das fi bras entre a junção miotendínea e zona de inervação mais próxima. Como rotina de trabalho adotamos a sugestão de Fukuda [23] e posicionamos os eletrodos no ponto médio entre o ângulo da mandíbula e o arco zigomático para o masseter e aproximadamente 50 mm à frente e 20 mm verticalmente ao trago da orelha para o temporal fi bras anteriores. Conforme preconizam Basmajian [24] e De Luca [22,25], foi avaliada a tensão RMS (Root Mean Square), valor que proporciona mais informações em relação à amplitude do sinal eletromiográfi co, pois fornece o número de unidades motoras ativadas (recrutamento motor), frequência de disparo das unidades motoras e a forma de potenciais de ação das unidades motoras (áreas).…”
Section: Eletromiografiaunclassified